Study on Genetic Diversity of Qilin Chicken Based on Complete Mitochondrial DNA D-loop Sequences - Weina LI; Meihui GUO; Jintian WEN; Zhuoxian WENG; Jiebo CHEN; Bingwang DU; Xunhe HUANG (Guangdong nongye kexue, 2023)
【Objective】The study was carried out to evaluate genetic diversity level of Qilin chicken inferred from complete mitochondrial DNA (mtDNA) D-loop sequences in order to clarify the bread formation of Qilin chicken.【Method】Three populations (yellow, white and black-feathered Qilin chickens) and eight indigenous chicken breeds were used for direct sequencing with PCR products of complete mtDNA D-loop region, and these sequences were then used to calculate the genetic variation and neutral test, to construct median networks of haplotypes and to investigate the breeding history of Qilin chickens.【Result】The length of mtDNA D-loop complete sequence ranged from 1 231 to 1 232 bp. The content of C+G (39.8%) was lower than that of T+A (60.2%). The total nucleotide diversity of Qilin chickens was 0.00630±0.00054, which was significantly higher than that of each of the eight indigenous chicken breeds. The haptype diversity and nucleotide diversity in yellow, white and black-feathered Qilin chickens were 0.777±0.076, 0.816±0.060, 0.710±0.057 and 0.00699±0.00115, 0.00662±0.00090, 0.00546±0.00062, respectively. The level of genetic diversity was positively correlated with population size. The K2P genetic distance and net genetic distance between Qilin chickens and eight indigenous chicken breeds ranged from 0.008 to 0.009 and 0.003 to 0.005, respectively, which were greater than those between the eight indigenous chicken breeds. A total of 45 mutation sites were detected in 90 samples of Qilin chickens. Seventeen haplotypes were defined in Qilin chickens, with eight exclusive haplotypes and haplotype diversity of 0.773±0.039. The numbers of haptypes of yellow, white and black-feathered Qilin chickens were 12, 7 and 5, respectively. Nineteen haplotypes were defined in eight adjacent indigenous chicken breeds, and no haplotype was shared with Qilin chickens. The number of haptypes of Hetian chicken (8) was greater than that of other chickens, and Ningdu yellow chicken only had three haptypes.The neutral test indicated that all chickens used in this study did not show obvious population expansion at the breed level, with the exception of black-feathered Qilin chickens. The haplotypes of Qilin chickens were distributed in clades A, B, C and E, and the dominated haplogroups were B (30.0%) and E (64.4%). The haplotypes of the eight indigenous chicken breeds were mainly distributed in clades A and B.【Conclusion】Unique haptypes indicated that Qilin chickens had an independent breed formation history, and the relatively higher level of genetic diversity of this breed will facilitate its protection and utilization.